2008
DOI: 10.3748/wjg.14.1521
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells in patients with inflammatory bowel diseases treated with adacolumn granulocytapheresis

Abstract: AIM:To investigate if the clinical efficacy of granulocytes and monocytes by adsorption (GMA) is associated with an increased frequency of peripheral regulatory T cells (Tregs), as these cells have proven to be successful in suppressing inflammatory bowel disease (IBD) in animal models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…Two research groups have reported independently a significant increase in circulating levels of the CD4 + CD25 high+ /FoxP3 phenotype following a course of GMA [43,44].…”
Section: Cd25mentioning
confidence: 99%
“…Two research groups have reported independently a significant increase in circulating levels of the CD4 + CD25 high+ /FoxP3 phenotype following a course of GMA [43,44].…”
Section: Cd25mentioning
confidence: 99%
“…+ cells may be persistent up to 10 weeks after treatment [21][22][23]. In our study we did not capture the precise duration of the increase in blood Treg.…”
Section: /Foxp3mentioning
confidence: 97%
“…More recently, alterations in T cell subsets has been associated with the beneficial effect of GMA. In particular, in UC a decrease in regulatory CD4 + T cells (Treg) in the intestinal mucosa and an increase in peripheral blood CD4 + Treg has been reported by several authors to correlate with a favourable clinical response [21][22][23]. Treg cells suppress proliferation and cytokine production of activated T cells and are known to play an important role in maintaining peripheral tolerance [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The decrea sed LECAM1expression on leucocytes impedes the leukotaxis to the inflamed tissue and CD10negative immature granulocytes appear in the peripheral blood [141,146,147] . Another effect to be mentioned is the removal of the peripheral DCs [148] and the leachate of regulatory Tcells (Tregs) [30,149,150] . Proinflammatory cytokines decrease while anti-inflammatory cytokines increase [151] .…”
Section: Granulocyte Monocyte Apheresismentioning
confidence: 99%